The Influence of Leadership Style and Work Environment on Organizational Commitment - Balya Iqbal; Umar Farouk; Sugiyanta; Jati Nugroho (Cita konsultindo, 2025)
This study aims to examine the correlation between leadership style and work environment with organizational commitment at PT Triangle Motorindo. The data collection methods utilized encompass surveys, interviews, observation, and literature review. The sampling approach employed is simple random sampling, computed using the Slovin formula, yielding a sample size of 75 respondents. The analytical tools used include instrument tests, classical assumption tests, multiple linear regression, and hypothesis testing. The data was processed using SPSS. The multiple linear regression analysis yielded the regression equation: Y = 24.918 + 0.268 X1 + 0.406 X2 + e. The results suggest that both leadership style and work environment have a large and beneficial impact on organizational commitment, both individually and together. The combined impact of leadership style and work environment accounts for 64.4% of the variability in organizational commitment, while the remaining 35.6% is attributed to other variables not considered in the study. An effective leadership style and a pleasant work environment have the potential to enhance organizational commitment.